Factors affecting bankruptcy: the case of Malaysia / Siti Halijah Mohd Noh - Mohd Noh, Halijah (2014)
This paper deals with the bankruptcy of individual subject and how bankruptcy rate is affected by macroeconomic variables. The data collected is based on the time series for the period from 2006 to 2013 on quarterly basis consist of the independent variables such as non performing loans, per capita income, unemployment and bankruptcy cases as dependent variables. There might be supposed positive or negative significant relationship between non performing loans, unemployment, per capita income (GNI) with bankruptcy cases in Malaysia. My finding in this paper research confirms strong correlation between non performing loans, unemployment with the number bankruptcies cases declared in Malaysia. This result shows that Malaysians fails to repay loan due to inability to settle their debt and also loss of work or being unemployment. While per capita incomes (GNI) have no significant relationship towards bankruptcy cases in Malaysia. This research is done by using Malaysia as single entity instead of a pool of countries.